Do Doctors Need Communication in their Job Places? (A Case in Indonesia) - Dwi Poedjiastutie; Ratih Puspitasari (IJEE (Indonesian Journal of English Education), 2018)
ABSTRACTThe current study revealed the communication needs of medical students at Universitas Muhammadiyah Malang (UMM). Three approaches of Need Analysis (NA) were combined in this study; Target Situation Analysis (TSA), Presentation Situation Analysis (PSA), and Pedagogical Need Analysis (PNA). The questionnaires were circulated to medical students. The findings discovered that communication skill was considered important in EMP course. The medical students realized the importance of doctors’ communication in order to enhance better performance in their professional settings. ESP teachers are supposed to give a model of communication; Students also expected that the materials should be authentic. The materials design should have clear and coherent objectives to help the students achieving the communication goals. Moreover, students want ESP teaching put them as close as possible to the workplace situation.  ABSTRAKPenelitian ini bertujuan untuk mengidentifikasi kebutuhan materi pembelajaran Bahasa Inggris  komunikasi pada mahasiswa kedokteran di Universitas Muhammadiyah Malang.  Pendekatan yang digunakan dalam penelitian ini adalah gabungan antara Target Situation Analysis (TSA), Presentation Situation Analysis (PSA), dan Pedagogical Need Analysis (PNA). Dari data yang diperoleh dalam penelitian ini ditemukan bahwa mahasiwa kedokteran merasa mata kuliah EMP (English for Medical Purposes) itu penting untuk menunjang karir dan profesi mereka. Maka dari itu para pengajar mata kuliah ESP (English for Specific Purposes) diharapkan bisa memberikan model-model materi pengajaran Bahasa Inggris untuk komunikasi yang otentik; yaitu materi yang tepat untuk mengasah ketrampilan mereka dalam komunikasi. Bahkan, para mahasiswa kedokteran menginginkan adanya model-model pengajaran ESP yang bisa membawa mereka ke situasi  semirip mungkin dengan dunia kerja mereka di kemudian hari.     How to Cite: Poedjiastutie, D., Puspitasari, R. (2018). Do Doctors Need Communication in Their Job Places? (A Case in Indonesia). IJEE (Indonesian Journal of English Education), 5(2), 127-142. doi:10.15408/ijee.v5i2.10134